Reasonable Incomplete Myocardial Revascularization in Patients with Chronic Heart Failure and Reduced Left Ventricular Ejection Fraction - Mariia V. Kucheriava; Georgiy B. Mankovsky (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To evaluate the results of incomplete myocardial revascularization with percutaneous coronary intervention (PCI) in patients with ischemic cardiomyopathy and heart failure with reduced left ventricular ejection fraction based on the residual SYNTAX Score (rSS) scale.Materials and methods. This prospective observational one-center study was conducted at the Ukrainian Children’s Cardiac Center, Clinic for Adults and included 192 patients whounderwent coronary angiography and myocardial re-vascularization using PCI. Baseline demographic and clinical parameters, including gender, age, presence of comorbid pathology were obtained from the medical history of each patient retrospectively. The results of revascularization were evaluated over a period of 2 years (from March 2020 to March 2022). To assess the completeness of revascularization, the rSS scale was used, and coronary angiography was repeated.Results and discussion. The most significant adverse events during 24 months of follow-up, associated with the severity of coronary artery damage according to the SYNTAX scale ≥23 points, were: death from any cause with odds ratio (OR) 6.9 (95% CI, p = 0.05); myocardial infarction (MI) with OR 5.5 (95% CI, p = 0.001); the combined endpoint was OR 2.4 (95% CI, p = 0.005). Over a 2-year follow-up period,results of myocardial revascularization according to the rSS scale were evaluated the effect of coronary artery stenting with minimal residual atherosclerotic narrowing (rSS ≤8) and significant arterial lesions (rSS ≥9) on indicators such as all-cause mortality, myocardial revascularization, re-hospitalization, recurrent acute MI and stroke were analyzed. Data analysis showed statistically significant difference in all indicators in favor of the group with a score of rSS ≤8 (р <0.05).Conclusions. The rSS scale in patients with coronary artery disease and heart failure with reduced left ventricular ejection fraction after PCI is a statistically significant criterion for the impact on the combined endpoint. In addition, an rSS score ≥9 was associated with a significantly higher riskof all-cause mortality, recurrent acute MI, and recurrent revascularization. A stratified rSS score ≥9 in ischemic cardiomyopathy with left ventricular ejection fraction ≤40% was more often observed in patients with existing comorbid pathology, such as hypertension, diabetes mellitus, stroke, peripheral artery disease.